Running practice improves mood state and sleep self-assessment (Research, Society and Development, 2021)
Sleep and mood states are psychological aspects influenced by the practice of physical exercise, thus, the objective of the research was to investigate the effect of 16 weeks of running in relation to the sleep self-assessment and changes in the states of humor. Eighteen recreational runners (13 Women; 5 Men) participated in the research. The Brunel Mood Scale (BRUMS) assessed Mood States, being transported before and after training, while the self-reported question about sleep was done just before training. Descriptive and inferential statistics were applied to assess the relationships between sleep, mood and running, differences were considered statistically significantly when p < 0.05. The results showed 5 dissipate from the mood variables anger, tension, distortion, confusion and fatigue, dissipate changes before and after the intervention, while vigor did not change. The effect size showed a large magnitude in reduction of anger and depression, moderate reduction in tension and confusion, negligible reduction in vigor, and a small increase in magnitude of fatigue. Regarding sleep self-assessment, there was no difference before and after the intervention. It can be observed that a moderate intensity street running practice can improve sleep quality and maintain adequate levels of mood.